1991
DOI: 10.1002/mpo.2950190215
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma with central nervous system metastasis: A case report and literature review

Abstract: In the United States and western Europe, hepatocellular carcinoma is not generally regarded as a distantly metastasizing tumor. The ability of hepatocellular carcinoma to metastasize to the brain is illustrated by the example of a 65-year-old white American man with no identifiable risk factors for primary liver cancer. Though hepatocellular carcinoma rarely metastasizes to the central nervous system, such metastases are reported to have led to tumor diagnosis or signaled tumor relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…6,7 In our case, no other secondary site of metastasis except isolated metastasis at the apical portion of the right lung was discovered. Although brain metastasis may arise from primary sites in various organs and tissues, they are frequently seen with bronchogenic, breast, and prostate cancers.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…6,7 In our case, no other secondary site of metastasis except isolated metastasis at the apical portion of the right lung was discovered. Although brain metastasis may arise from primary sites in various organs and tissues, they are frequently seen with bronchogenic, breast, and prostate cancers.…”
Section: Discussionmentioning
confidence: 70%
“…The cytomorphology of intracranial metastases of HCC received little attention in previous reports, which concentrated mostly on the clinical aspects. 6,8 Cytologically, the tumor cells have an appearance similar to that seen in histologic sections. There are frequently cohesive clusters with a suggestion of trabecular formation of abnormal liver cells lined by sinusoidal cells have been reported.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Spontaneous EDH due to dural metastasis of hepatocellular carcinoma is very rare and to the authors' knowledge, it has been reported only 6 cases in the literature 5,10,12,[15][16][17] . It has been well known that hepatocellular carcinoma has a characteristic of high risk of bleeding tendency due to hepatic failure and formation of neoangiogenesis 6) . It usually spreads to regional lymph nodes around the porta hepatis via lymphatics, but it can also spread hematogenously via intrahepatic vein, portal vein, and hepatic artery.…”
Section: Discussionmentioning
confidence: 99%
“…We report herein a patient with hepatocellular carcinoma (HCC) who was suspected of having spinal lesions based on neurological findings, and a metastatic spinal tumor could be diagnosed by imaging examination. Since there have been very few case reports of spinal metastasis from HCC [1][2][3] , we report this case with discussion of the literature.…”
Section: Introductionmentioning
confidence: 99%